Utility Assessment of Isolated Starch and Extract from Thai Yam (Dioscorea hispida Dennst.) for Cosmetic via In Vitro and In Vivo Studies - Suthinee Sangkanu; Jiraporn Khanansuk; Sathianpong Phoopha; Wandee Udomuksorn; Thitiporn Phupan; Jirapa Puntarat; Sucharat Tungsukruthai; Sukanya Dej-adisai (Life)
In Thailand, wild yam, or Dioscorea hispida Dennst., is a starchy crop that is usually underutilized in industry. The purpose of this study was to isolate the starch and extract the phytochemical from D. hispida and use them in cosmetics. Starch was used instead of talcum, which can cause pulmonary talcosis in dusting powder formulas (DP 1-5). GC-MS was used to identify the bioactive components present in the ethanolic extract of D. hispida. The main compounds were identified as 9,12-octadecadienoic acid (Z,Z)- (6.51%), stigmasta-5,22-dien-3-ol, (3.beta.,22E)- (6.41%), linoleic acid ethyl ester (5.72%), (Z,Z)-9,12-octadeca-dienoic acid, 2,3-dihydroxy-propyl (3.89%), and campesterol (3.40%). Then, the extract was used as an ingredient in facial sleeping mask gel formulas (SM 1–SM 5). Stability tests, physical characteristics, enzyme inhibitions, and sensitization dermal toxicity tests were used to evaluate the DP and SM formulations. The results showed that the fresh tubers of D. hispida showed a 12.5% w/w starch content. The findings demonstrated that starch powder had a restricted size distribution, ranging from 2 to 4 μm, and a smooth surface that was polygonal. Following stability testing, the color, odor, size, and flowability of all DP formulations did not significantly differ. The SEM investigation revealed that DP particles were homogenous. For the sensitization dermal toxicity test, DP denoted no erythema or skin irritation in the guinea pigs. After stability testing, the colors of the SM formulas were deeper, and their viscosity slightly increased. The pH did not significantly change. After the stability test, SM formulas that contained Glycyrrhiza glabra and D. hispida extracts exhibited stable tyrosinase and elastase inhibitory activities, respectively. In the sensitization dermal toxicity test, guinea pigs showed skin irritation at level 2 (not severe) from SM, indicating that redness developed. All of these findings indicate that D. hispida is a plant that has potential for use in the cosmetics industry. Furthermore, D. hispida starch can be made into a beauty dusting powder, and more research should be conducted to develop an effective remedy for patients or those with skin problems.